THE INFLUENCE OF MANAGERIAL OWNERSHIP ON TAX AVOIDANCE - Nofianti, Nana; Mulyasari, Windu; Anggit, Muhammad (Management Science Research Journal, 2022)
This study aims to determine the effect of managerial ownership on tax avoidance with hedging decisions as an intervening variable. The independent variable in this study is managerial ownership which is measured by the total share ownership owned by the management divided by the total outstanding shares of the company. The dependent variable used in this study is tax avoidance as measured by the Cash Effective Tax Rate. The population of this study on manufacturing companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The sampling technique used in this research is purposive sampling method with a total sample of 49 research data. The results of this study indicate that managerial ownership has no effect on tax avoidance.